An exploration of the solution of direct methanol fuel cell cost effectiveness - Wang, Tengyi; Luo, Zhiwei; Wang, Changsheng; Li, Yang; Chen, Xi; Tang, Yang; Wang, Xinsheng; Zhou, Zhiquan (Frontiers in Chemistry, 2024)
The work in this paper incorporated printed circuit board (PCB) technology into micro-direct methanol fuel cells (µDMFCs) and conjectured and verified the performance degradation factors of PCB current collectors in µDMFCs by testing different designed configuration µDMFCs. The experiment results showed that all kinds of PCB coating can benefit from the porous stainless-steel plates covering to a great extent. At the end of 48 h discharging, µDMFCs with porous stainless-steel plates between MEA and PCB coating achieved higher performance than those of the direct contacting series. It can be inferred from various types of experimental data that because of stainless-steel porous plate isolating, the impact of corrosion on the surface of the PCB electrode plate was reduced to a certain extent. The corrosion of the electrode plate was slowed down in the µDMFC discharging as a result of the passivation behavior on the iron surface and a decrease in corrosion current. Consequently, the attenuation of the PCB performance was delayed. The conclusion of this work explores a practical direction to enhance the cost-effectiveness of fuel cells, promoting the large-scale application of DMFCs in the future.